The Arab Gulf issues in the debates of the Iraqi Parliament (1958-1950), a study Documentary (Journal of the College of Basic Education, 2023)
The Arabian Gulf occupied a special importance for Iraq, as it is the only sea outlet overlooking theIt is not surprising that Iraq's relations with the regions of the Arabian Gulf continued through eras.different history, and then it was natural for the Iraqi public opinion to express his feelings about what is going onevents in those countries, with the opinions that his deputies used to put forward during the sessions of the Council of Representatives, and what was going on in themFrom discussions of foreign policy issues that successive Iraqi governments dealt with, especiallyWith regard to Arab issues, which took precedence over all other topics for discussion, because they representnational obsession rooted in the hearts of Iraqis, and thus took a large part of those discussions, due to the growingThat Arab spirit among the people of Iraq, which extends in its historical roots to earlier periods.for the research topic.Despite the Iraqis' preoccupation with the Palestinian cause and the issue of Arab unity and support for thenational liberation in the Maghreb during the fifties of the twentieth century, but they were notFar from what is happening in the Arab Gulf countries, however, the official position represented by the governmentssuccessive Iraqis, did not give the Arab Gulf issues the required attention compared to the popular stance thatMembers of the House of Representatives rejected it, due to Iraq’s association with the 1930 treaty with Britain, which restrictedHis independence, and what followed that from his accession to the Baghdad Pact in 1955, which made the positions ofIts governments are far from fulfilling its national obligations as stipulated in the Arab League Charter and the Defense Treaty.The Arab Commonwealth of 1950. In the light of these facts, it becomes clear to us that the opinions and ideas put forward by the representativesIn the debates of the House of Representatives, which appeared between the lines of its documented records, and the demand to pay attention to the issues ofthe Arabian Gulf, as a result of the great dangers threatening it related to the objectives of British policy and its interests inThe region, and the Iranian ambitions in some of its emirates, did not receive a deaf ear from those governments, whichIt was afraid of angering the British side, and Iraq did not show any initiative or move towards activating its role.political events about the events that the Arab Gulf region was exposed to, with the need to remember that what the research mentionedSome of the propositions in those parliamentary discussions were expressing the Iraqi public opinion, which is completely different from the Iraqi public opinion.The official position, whose policies we clarified.